Assessment of the antibacterial activity of four essential oils and the biobactericide Neco. - Jean-Fabrice Yala; Rolande Mabika Mabika; Brahima Camara; Seydou Tuo; Alain Souza; Alexis Nicaise Lepengue; Daouda Koné; Bertrand M’batchi (International Journal of Phytomedicine, 2017)
The purpose of this study was to assess in vitro the activity of four essential oils (Cymbopogon citratus, Eucalyptus citriodora, Lippia multiflora, Melaleuca quinquenervia) and the biobactericide Neco® on Gram-positive bacteria. The aromatogram and antibiogram were assessed by the agar well diffusion method and the Muller Hinton disk-agar diffusion method, respectively. Also, the minimum inhibitory concentration and the minimum bactericidal concentration were determined by the microdilution method in liquid medium. The aromatogram showed that the biobactericide Neco® induced the largest inhibition diameters (34.53 ± 11.82 - 43.92 ± 5.38 mm) of all strains combined, followed by the essential oils of Eucalyptus Citriodora (30.01 ± 3.02 - 41.89 ± 1.77 mm) and Lippia multiflora (20.72 ± 4.72 - 37.61 ± 2.80 mm). However, the essential oils of Melaleuca quinquenervia (19.99 ± 3.93 - 26.20 ± 13.27 mm) and Cymbopogon citratus (13.52 ± 3.59 - 29.08 ± 2.35 mm) had the smallest inhibition diameters. Moreover, the comparison of the activities of the aromatogram and antibiogram revealed generally that activities were higher with essential oils than with antibiotics. At the end of this study, the essential oils of Cymbopogon citratus, Eucalyptus citriodora, Lippia multiflora, Melaleuca quinquenervia and the biobactericide Neco® had an antibacterial activity on Gram+ bacteria.